On Accelerated Degradation of DC-Link Film Capacitors and Data-Based Lifetime Estimation - Angel Pena-Quintal; Uvais Mustafa; Chris Gerada; Md Rishad Ahmed (IEEE Access)
Methods to address the lifetime of film capacitors are a new trend, which have come about due to the importance of control algorithms relying on the stability and the reliability of this passive device for controlling ever-increasing power with optimal power conversion efficiency in modern powertrains of electrical vehicles. Capacitance degradation over time is a key-parameter to determine the lifetime of an electric vehicle drive and to provide safety to the passengers. In this paper, a method to account for the degradation of film capacitors is presented considering a charge-and-discharge method at a steady temperature to better understand its capacitance and equivalent series resistor changing behaviour. The temperature of the capacitor is set at a maximum rated level (from the manufacturer information) to assess an accelerated degradation, to address the physics of failure for these film capacitors and to propose a lifetime estimation method for them.